From distrust to trust : Balancing between forcing and fostering management control systems in a hostile cross-border post-acquisition integration - Vuorenmaa, Erkki (Elsevier, 2025)
Extant research contends that in a context characterised by distrust, partners do not engage in developing trust in each other, and the use of management control systems creates tensions and increases distrust. This begs the questions of whether and how trust can be promoted and management control exercised in such a context. Thus, this paper examines the interplay between management control systems and (dis)trust in a hostile post-acquisition integration of two global companies. In doing so, this paper provides a detailed analysis of the role of management control systems as well as the underlying motives and the consequences of their use in various integration processes at different organisation levels. Applying the labour–management negotiation strategy theory, this study distinguishes between two modes of implementing management control. First, in the forcing mode, management control systems are used to coerce and monitor employees and instil top-down organisational values in them to promote controllability. Second, in the fostering mode, management control systems are exercised to promote mutual benefits, learning and shared values to support cooperation. The results show that the combined use of forcing and fostering management control systems supports the development of trust in the post-acquisition context characterised by distrust. Forcing control promotes trust by providing stability, creating accountability for cooperative achievements and supporting conflict resolution, whereas fostering control develops trust by facilitating goal sharing, mutual learning and value integration. This study advances the knowledge of management control systems and the relation between (dis)trust and control in the post-acquisition integration context by demonstrating why and how managers balance between forcing and fostering controls and how these control modes, separately and in combination, interact with (dis)trust.